Analisis Komparatif Kinerja Keuangan Sebelum dan Setelah Penerapan PSAK 73 atas Sewa - Dewi; Sri Fadilah (Bandung Conference Series: Accountancy, 2023)
Abstract. Changes in accounting standards will cause differences in the company's financial performance. This study aims to determine the differences in financial performance before and after the implementation of PSAK 73. The population in this study were service companies in the infrastructure, utilities and transportation sectors listed on the Indonesia Stock Exchange for the 2019-2020 period. Sampling in the study using purposive sampling method, and obtained 28 company samples. The research method used is a comparative descriptive and verification method with a quantitative approach. The indicators used to determine financial performance before and after the implementation of PSAK 73 include financial ratio analysis Current ratio, Debt to Asset Ratio, Debt to Equity Ratio, Return on Asset and Return on Equity. Hypothesis testing was carried out using the Wilcoxon signed rank test with SPSS 23. The results showed that after the implementation of PSAK 73, some companies experienced a decrease in Current Ratio, Debt to Equity Ratio and Return on Asset. Meanwhile, the Debt to Asset Ratio and Return on Equity ratio have increased. In hypothesis testing using the wilcoxon test, it shows that there is a difference between before and after the application of PSAK 73 in the Current ratio, Debt to Asset Ratio, Return on Asset, and Return on Equity, while in the Debt to Equity Ratio ratio there is no difference before and after the application of PSAK 73. Abstrak. Perubahan standar akuntansi akan menyebabkan perbedaan pada kinerja keuangan perusahaan. Penelitian ini bertujuan untuk mengetahui perbedaan kinerja keuangan sebelum dan setelah diterapkannya PSAK 73. Populasi dalam penelitian ini adalah perusahaan jasa sektor infrastruktur, utilitas, dan transportasi yang terdaftar di Bursa Efek Indonesia periode 2019-2020. Pengambilan sampel dalam penelitian menggunakan metode purposive sampling, dan didapat 28 sampel perusahaan. Metode penelitian yang digunakan adalah metode deskriptif komparatif dan verifikatif dengan pendekatan kuantitatif. Adapun indikator yang digunakan untuk mengetahui kinerja keuangan sebelum dan setelah penerapan PSAK 73 meliputi analisis rasio keuangan Current ratio, Debt to Asset Ratio, Debt to Equity Ratio, Return on Asset dan Return on Equity. Pengujian hipotesis dilakukan menggunakan uji wilcoxon signed rank dengan SPSS 23. Hasil penelitian menunjukkan bahwa setelah penerapan PSAK 73 sebagian perusahaan mengalami penurunan pada Current Ratio, Debt to Equity Ratio dan Return on Asset. Sedangkan pada rasio Debt to Asset Ratio dan Return on Equity mengalami peningkatan. Dalam pengujian hipotesis menggunakan uji wilcoxon menunjukan terdapat perbedaan antara sebelum dan setelah penerapan PSAK 73 pada rasio Current ratio, Debt to Asset Ratio, Return on Asset, dan Return on Equity, sedangkan pada rasio Debt to Equity Ratio tidak terdapat perbedaan pada sebelum dan setelah penerapan PSAK 73.